2017
DOI: 10.1128/aem.03028-16
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Persistence in Tomatoes Requires a Distinct Set of Metabolic Functions Identified by Transposon Insertion Sequencing

Abstract: Human enteric pathogens, such as Salmonella spp. and verotoxigenic Escherichia coli, are increasingly recognized as causes of gastroenteritis outbreaks associated with the consumption of fruits and vegetables. Persistence in plants represents an important part of the life cycle of these pathogens. The identification of the full complement of Salmonella genes involved in the colonization of the model plant (tomato) was carried out using transposon insertion sequencing analysis. With this approach, 230,000 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 59 publications
3
98
0
Order By: Relevance
“…We used two global approaches to discover Salmonella genes that affect the P22 lytic life cycle. First, a library of random integrations of a transposon (Tn) into bacterial genomes was employed, a technique that can identify genes under selection in various growth conditions (Sassetti et al, 2001;Canals et al, 2012;de Moraes et al, 2017). We used a high complexity Tn5 library of S. enterica serovar Typhimurium strain 14028s to identify either genes whose products enable or promote phage infection (mutation resulted in blocked or delayed infection by P22) or genes that increased bacterial host resistance to P22 infection (mutation resulted in faster loss of host DNA, likely as a result of increased phage propagation).…”
Section: Global Analysis Of Salmonella Genes That Affect Phage P22 Lymentioning
confidence: 99%
See 2 more Smart Citations
“…We used two global approaches to discover Salmonella genes that affect the P22 lytic life cycle. First, a library of random integrations of a transposon (Tn) into bacterial genomes was employed, a technique that can identify genes under selection in various growth conditions (Sassetti et al, 2001;Canals et al, 2012;de Moraes et al, 2017). We used a high complexity Tn5 library of S. enterica serovar Typhimurium strain 14028s to identify either genes whose products enable or promote phage infection (mutation resulted in blocked or delayed infection by P22) or genes that increased bacterial host resistance to P22 infection (mutation resulted in faster loss of host DNA, likely as a result of increased phage propagation).…”
Section: Global Analysis Of Salmonella Genes That Affect Phage P22 Lymentioning
confidence: 99%
“…We used a high complexity Tn5 library of S. enterica serovar Typhimurium strain 14028s to identify either genes whose products enable or promote phage infection (mutation resulted in blocked or delayed infection by P22) or genes that increased bacterial host resistance to P22 infection (mutation resulted in faster loss of host DNA, likely as a result of increased phage propagation). This 14028s Tn5 library contained 240,000 mutants, and insertions were present at an average density of about one every 25 bp and an average of 42.5 per gene (de Moraes et al, 2017). Almost all non-essential genes were represented by multiple independent insertions at different locations.…”
Section: Global Analysis Of Salmonella Genes That Affect Phage P22 Lymentioning
confidence: 99%
See 1 more Smart Citation
“…Some similar metabolic functions associated with Salmonella colonization in animals (mouse) and plants (tomato) have been identified, such as biosynthesis of fatty acids, lipopolysaccharides (LPSs) and nucleotides. Lipopolysaccharides have a protective role in the immunity mechanisms of animals and plants . Other researchers have found that Salmonella fimbriae are required for successful attachment in a plant cell wall model …”
Section: Resultsmentioning
confidence: 99%
“…Lipopolysaccharides have a protective role in the immunity mechanisms of animals and plants. 14 Other researchers have found that Salmonella fimbriae are required for successful attachment in a plant cell wall model. 15 The attachment percentages found in our study are similar to those reported in tomato (0.8%), green tomato (1.3%), small green tomato (0.2%), and peach (3.0%).…”
Section: Ability Of Individual Salmonella Strains To Attach and Colonmentioning
confidence: 98%